2017
DOI: 10.1093/tropej/fmw084
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Pruritus in an 18-Month-Old Male Infant Due to Anicteric Cholestasis

Abstract: An 18-month-old male infant was referred to us with pruritus from 6 months of age. He was being managed as atopic eczema with emollients and antihistamines without any response to treatment. On examination, he was found to have extensive scratch marks, mild hepatomegaly and no icterus. Blood investigations were suggestive of anicteric cholestatic liver disease. Liver biopsy was suggestive of progressive familial intrahepatic cholestasis type 3. He showed symptomatic improvement after starting ursodeoxycholic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Only few cases of PFIC are reported in the literature, under no circumstances in association with AD 9 10. We concluded that this patient is a rare case of comorbidity between AD and type 2 progressive familial intrahepatic cholestasis (PFIC2).…”
Section: Discussionmentioning
confidence: 73%
“…Only few cases of PFIC are reported in the literature, under no circumstances in association with AD 9 10. We concluded that this patient is a rare case of comorbidity between AD and type 2 progressive familial intrahepatic cholestasis (PFIC2).…”
Section: Discussionmentioning
confidence: 73%